Use of Fruit Waste as Natural Dyes in pH-Sensitive Colorimetric Sensors for Tilapia Fillets Quality Decline - Audrynachristie, Brigitta Stella; Alamsjah, Mochammad Amin; Kismiyati (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research 1. The use of dragon fruit peel, mangosteen peel and onion peel waste as natural dyes in colorimetric sensors was analyzed in this study. 2. Natural dyes are added to bioplastics with kappa carrageenan polymer, a mixture of corn starch and kappa carrageenan, and corn starch to determine the characteristics of the best bioplastic to be used as a colorimetry sensor. 3. The quality of the fish fillet compared to the color changes in colorimetry sensor was analysed in this study. 4. Mixture of kappa carrageenan and corn starch as bioplastic with casting method was analyzed in this study. Abstract Tilapia fillet aimed to prolonging shelf life, may still experience quality deterioration posing food safety risks. Colorimetric pH indicators offer a simple and affordable solution to the food industry to evaluating fish spoilage. Natural dyes reduce potential health risks associated with synthetic dyes. Anthocyanin sources which haven’t been explored like dragon fruit rind, mangosteen rind, and red onion skin serve as real time quality and safety assessment tools for consumers. This study explores the potential of anthocyanin extracted from dragon fruit rind, mangosteen rind, and red onion skin as colorimetric sensors for evaluating the quality and safety of tilapia fillets. The anthocyanin-based sensors developed using kappa carrageenan and corn starch polymers to achieve sustainability fisheries program and were characterized according to the Japanese Industrial Standard for bioplastics. The results show that anthocyanin from dragon fruit skin exhibited the best color change in response to pH changes in the tilapia fillet, indicating its potential as a reliable indicator of spoilage. This research highlights the feasibility of using natural dyes as colorimetric sensors, reducing the risk of health hazards associated with synthetic dyes. This study also shows that different polymers give different characteristic of bioplastic. Carrageenan bioplastic shows best thickness values of 0,118 mm; Carrageenan and corn starch bioplastics show best tensile strength values of 20,62 MPa; Carrageenan bioplastic shows best elongation values of 254%; and all polymers show the same biodegradation rate values of 14,29%. Further studies are needed to explore other natural dyes and optimize the polymers for optimal bioplastic characteristics.